(untitled) (Journal of Philosophy, Culture and Political Science, 2021)
Three central ideas in contemporary liberal political philosophy include: 1) liberty and equality represent the most basic political values; 2) legitimate political authority must be exercised on the basis of moral reasons that are compatible with liberty and equality; and 3) the burden of justification for political authority is on the state, not the individuals subject to the state’s coercive authority. Notwithstanding many different interpretations of liberalism that range from libertarian, egalitarian, and social democratic formulations, liberal political philosophers base their various positions on these fundamental ideas.[i] Religious freedom, toleration, and a guarantee of equal treatment under law are among the widely shared convictions endorsed by liberal political philosophers. In this paper I propose an approach to thinking about religion and politics that should inform how we think about liberalism and religion. I also consider how the conception of political authority defended by the prominent Muslim public intellectual Abdullahi Ahmed An-Na’im[ii] is a paradigm example of liberalism. In Part I I consider two approaches to religion and politics. According to the reductionist view, whether values that are central to a religious tradition can be reconciled to liberalism is more a matter of doctrine than practice. By contrast a non-reductionist approach emphasizes that the relationship between political and religious values is influenced by a number of variables in addition to religious doctrine, including ethnicity, historical memory, political economy, and local politics. On this view, the path between religious and political convictions is anything but a straight line. In Part II I examine central arguments in An-Na’im’s work that are central to his version of liberalism, with a focus on liberty of conscience and religious freedom. To illustrate An-Na’im’s liberalism I focus on examples of claims about morality and theology, politics, and history. I conclude in Part III by considering how An-Na’im’s position is one example of what we would expect from a non-reductionist understanding of religion and politics. Key words: liberalism, religion, politics, secularism, Muslims.